Why is the derivative of x^n, nx^(n-1)?

From the definition of a derivative: f'(x) = lim h->0 ((f(x+h) - f(x)) / h) Let f(x) = x^n --> d\dx x^n = lim h->0 (((x+h)^n - x^n) / h) By binomial expansion, (x+h)^n = x^n + nhx^(n-1) + n(n-1)h^2 x^(n-2) + ... + h^n --> d\dx x^n = lim h->0 ((x^n + nhx^(n-1) + n(n-1)h^2 x^(n-2) + ... + h^n - x^n) / h) = lim h->0 (nx^(n-1) + n(n-1)h x^(n-2) + ... + h^(n-1)) = nx^(n-1)

Answered by Joshua F. Maths tutor

3646 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

A curve has equation x^2 + 2xy – 3y^2 + 16 = 0. Find the coordinates of the points on the curve where dy/dx =0


A 10 kilogram block slides down a 30 degree inclined slope, the slope has a coefficient of friction of 0.2. Calculcate the blocks acceleration down the slope.


Can you differentiate y = (x^4 + x)^10


Integrate 2sin^3(x)+3.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences